Vocal cord dysfunction: Does laryngeal adduction on laryngoscopy predict disease severity and response to laryngeal retraining therapy? - David Ahmadian; Nader Wehbi; Claire M. Gleadhill; Natalie Monahan; Charles J. Gallego; Jonathan R. Skirko; Helena T. Yip (Laryngoscope Investigative Otolaryngology)
Abstract Introduction Vocal cord dysfunction (VCD) is a complex disorder characterized by episodic adduction of the vocal folds during inspiration and expiration, which can lead to dyspnea, wheezing, cough, and acute‐onset respiratory distress. Currently, there is a lack of standardized criteria among treating physicians across multiple disciplines, including otolaryngologists, pulmonologists, allergists, and speech and language pathologists, for diagnosis and treatment of VCD, although laryngeal‐respiratory retraining therapy (LRT) has emerged as the preferred treatment modality. Objective In the present study, we examined the efficacy of LRT in patients presenting with a clinical diagnosis of VCD in the presence and absence of laryngeal adduction on laryngoscopy. Results Overall, 74.1% of the cohort showed a response to LRT, of which 62.1% were partial and 12.1% were significant responses. When comparing between patients with and without laryngeal adduction on laryngoscopy, there were no significant differences in the number of sessions of LRT undertaken, mean time to response, and overall response rate between the groups. Conclusion Our findings suggest that LRT should be utilized for all patients presenting with symptoms of VCD, even in the absence of laryngeal adduction on laryngoscopy.